Answer:
answer is 2
Step-by-step explanation:
can you mark me brainlist
Bernardo travels the same distance at 25mph as he does at 50mph. However, since 25mph is only half of 50 mph, he must travel twice as long at 25mph. If you call the time he traveled 50mph "t", then
<span>t+2t=3 </span>
<span>3t=3 </span>
<span>t=1 </span>
<span>This means he traveled 1 hour at 50mph. In this time, he traveled 50 miles. He traveled the same distance at 25mph, so his total distance was </span>
<span>50miles+50miles=100miles </span>
<span>so the round trip was 100 miles.</span>
AnswA line can be written in the form y = mx + b where m is the slope and b is the y intercept.
Since the slope is given as 4, the equation will be y = 4x + b
Plugging in the point (2,1) to the equation we get 1 = 4(2) + b or 1 = b + 8
Solving for b gives b = -7 so the equation will be y = 4x - 7er:
Step-by-step explanation:
angle AOB = 132 and is also the sum of angles AOD and
DOB. Hence
angle AOD + angle DOB = 132° ---> 1
angle COD = 141 and is also the sum of angles COB and BOD. Hence
angle COB + angle DOB = 141° ---> 2
Now we add the left sides together and the right sides of equations 1 and 2
together to form a new equation.
angle AOD + angle DOB + angle COB + angle DOB = 132 + 141 ---> 3
We should also note that:
angle AOD + angle DOB + angle COB = 180°
Therefore substituting angle AOD + angle DOB + angle COB in equation 3 by 180
and solving for angle DOB:
180 + angle DOB = 132 + 141
angle DOB = 273 - 180 = 93°
If you're using the app, try seeing this answer through your browser: brainly.com/question/3242555——————————
Solve the trigonometric equation:
![\mathsf{\sqrt{2\,tan\,x\,cos\,x}-tan\,x=0}\\\\ \mathsf{\sqrt{2\cdot \dfrac{sin\,x}{cos\,x}\cdot cos\,x}-tan\,x=0}\\\\\\ \mathsf{\sqrt{2\cdot sin\,x}=tan\,x\qquad\quad(i)}](https://tex.z-dn.net/?f=%5Cmathsf%7B%5Csqrt%7B2%5C%2Ctan%5C%2Cx%5C%2Ccos%5C%2Cx%7D-tan%5C%2Cx%3D0%7D%5C%5C%5C%5C%20%5Cmathsf%7B%5Csqrt%7B2%5Ccdot%20%5Cdfrac%7Bsin%5C%2Cx%7D%7Bcos%5C%2Cx%7D%5Ccdot%20cos%5C%2Cx%7D-tan%5C%2Cx%3D0%7D%5C%5C%5C%5C%5C%5C%20%5Cmathsf%7B%5Csqrt%7B2%5Ccdot%20sin%5C%2Cx%7D%3Dtan%5C%2Cx%5Cqquad%5Cquad%28i%29%7D)
Restriction for the solution:
![\left\{ \begin{array}{l} \mathsf{sin\,x\ge 0}\\\\ \mathsf{tan\,x\ge 0} \end{array} \right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%20%5Cbegin%7Barray%7D%7Bl%7D%20%5Cmathsf%7Bsin%5C%2Cx%5Cge%200%7D%5C%5C%5C%5C%20%5Cmathsf%7Btan%5C%2Cx%5Cge%200%7D%20%5Cend%7Barray%7D%20%5Cright.)
Square both sides of
(i):
![\mathsf{(\sqrt{2\cdot sin\,x})^2=(tan\,x)^2}\\\\ \mathsf{2\cdot sin\,x=tan^2\,x}\\\\ \mathsf{2\cdot sin\,x-tan^2\,x=0}\\\\ \mathsf{\dfrac{2\cdot sin\,x\cdot cos^2\,x}{cos^2\,x}-\dfrac{sin^2\,x}{cos^2\,x}=0}\\\\\\ \mathsf{\dfrac{sin\,x}{cos^2\,x}\cdot \left(2\,cos^2\,x-sin\,x \right )=0\qquad\quad but~~cos^2 x=1-sin^2 x}](https://tex.z-dn.net/?f=%5Cmathsf%7B%28%5Csqrt%7B2%5Ccdot%20sin%5C%2Cx%7D%29%5E2%3D%28tan%5C%2Cx%29%5E2%7D%5C%5C%5C%5C%20%5Cmathsf%7B2%5Ccdot%20sin%5C%2Cx%3Dtan%5E2%5C%2Cx%7D%5C%5C%5C%5C%20%5Cmathsf%7B2%5Ccdot%20sin%5C%2Cx-tan%5E2%5C%2Cx%3D0%7D%5C%5C%5C%5C%20%5Cmathsf%7B%5Cdfrac%7B2%5Ccdot%20sin%5C%2Cx%5Ccdot%20cos%5E2%5C%2Cx%7D%7Bcos%5E2%5C%2Cx%7D-%5Cdfrac%7Bsin%5E2%5C%2Cx%7D%7Bcos%5E2%5C%2Cx%7D%3D0%7D%5C%5C%5C%5C%5C%5C%20%5Cmathsf%7B%5Cdfrac%7Bsin%5C%2Cx%7D%7Bcos%5E2%5C%2Cx%7D%5Ccdot%20%5Cleft%282%5C%2Ccos%5E2%5C%2Cx-sin%5C%2Cx%20%5Cright%20%29%3D0%5Cqquad%5Cquad%20but~~cos%5E2%20x%3D1-sin%5E2%20x%7D)
![\mathsf{\dfrac{sin\,x}{cos^2\,x}\cdot \left[2\cdot (1-sin^2\,x)-sin\,x \right]=0}\\\\\\ \mathsf{\dfrac{sin\,x}{cos^2\,x}\cdot \left[2-2\,sin^2\,x-sin\,x \right]=0}\\\\\\ \mathsf{-\,\dfrac{sin\,x}{cos^2\,x}\cdot \left[2\,sin^2\,x+sin\,x-2 \right]=0}\\\\\\ \mathsf{sin\,x\cdot \left[2\,sin^2\,x+sin\,x-2 \right]=0}](https://tex.z-dn.net/?f=%5Cmathsf%7B%5Cdfrac%7Bsin%5C%2Cx%7D%7Bcos%5E2%5C%2Cx%7D%5Ccdot%20%5Cleft%5B2%5Ccdot%20%281-sin%5E2%5C%2Cx%29-sin%5C%2Cx%20%5Cright%5D%3D0%7D%5C%5C%5C%5C%5C%5C%20%5Cmathsf%7B%5Cdfrac%7Bsin%5C%2Cx%7D%7Bcos%5E2%5C%2Cx%7D%5Ccdot%20%5Cleft%5B2-2%5C%2Csin%5E2%5C%2Cx-sin%5C%2Cx%20%5Cright%5D%3D0%7D%5C%5C%5C%5C%5C%5C%20%5Cmathsf%7B-%5C%2C%5Cdfrac%7Bsin%5C%2Cx%7D%7Bcos%5E2%5C%2Cx%7D%5Ccdot%20%5Cleft%5B2%5C%2Csin%5E2%5C%2Cx%2Bsin%5C%2Cx-2%20%5Cright%5D%3D0%7D%5C%5C%5C%5C%5C%5C%20%5Cmathsf%7Bsin%5C%2Cx%5Ccdot%20%5Cleft%5B2%5C%2Csin%5E2%5C%2Cx%2Bsin%5C%2Cx-2%20%5Cright%5D%3D0%7D)
Let
![\mathsf{sin\,x=t\qquad (0\le t](https://tex.z-dn.net/?f=%5Cmathsf%7Bsin%5C%2Cx%3Dt%5Cqquad%20%280%5Cle%20t%3C1%29%7D)
So the equation becomes
![\mathsf{t\cdot (2t^2+t-2)=0\qquad\quad (ii)}\\\\ \begin{array}{rcl} \mathsf{t=0}&\textsf{ or }&\mathsf{2t^2+t-2=0} \end{array}](https://tex.z-dn.net/?f=%5Cmathsf%7Bt%5Ccdot%20%282t%5E2%2Bt-2%29%3D0%5Cqquad%5Cquad%20%28ii%29%7D%5C%5C%5C%5C%20%5Cbegin%7Barray%7D%7Brcl%7D%20%5Cmathsf%7Bt%3D0%7D%26%5Ctextsf%7B%20or%20%7D%26%5Cmathsf%7B2t%5E2%2Bt-2%3D0%7D%20%5Cend%7Barray%7D)
Solving the quadratic equation:
![\mathsf{2t^2+t-2=0}\quad\longrightarrow\quad\left\{ \begin{array}{l} \mathsf{a=2}\\ \mathsf{b=1}\\ \mathsf{c=-2} \end{array} \right.](https://tex.z-dn.net/?f=%5Cmathsf%7B2t%5E2%2Bt-2%3D0%7D%5Cquad%5Clongrightarrow%5Cquad%5Cleft%5C%7B%20%5Cbegin%7Barray%7D%7Bl%7D%20%5Cmathsf%7Ba%3D2%7D%5C%5C%20%5Cmathsf%7Bb%3D1%7D%5C%5C%20%5Cmathsf%7Bc%3D-2%7D%20%5Cend%7Barray%7D%20%5Cright.)
![\mathsf{\Delta=b^2-4ac}\\\\ \mathsf{\Delta=1^2-4\cdot 2\cdot (-2)}\\\\ \mathsf{\Delta=1+16}\\\\ \mathsf{\Delta=17}](https://tex.z-dn.net/?f=%5Cmathsf%7B%5CDelta%3Db%5E2-4ac%7D%5C%5C%5C%5C%20%5Cmathsf%7B%5CDelta%3D1%5E2-4%5Ccdot%202%5Ccdot%20%28-2%29%7D%5C%5C%5C%5C%20%5Cmathsf%7B%5CDelta%3D1%2B16%7D%5C%5C%5C%5C%20%5Cmathsf%7B%5CDelta%3D17%7D)
![\mathsf{t=\dfrac{-b\pm\sqrt{\Delta}}{2a}}\\\\\\ \mathsf{t=\dfrac{-1\pm\sqrt{17}}{2\cdot 2}}\\\\\\ \mathsf{t=\dfrac{-1\pm\sqrt{17}}{4}}\\\\\\ \begin{array}{rcl} \mathsf{t=\dfrac{-1+\sqrt{17}}{4}}&\textsf{ or }&\mathsf{t=\dfrac{-1-\sqrt{17}}{4}} \end{array}](https://tex.z-dn.net/?f=%5Cmathsf%7Bt%3D%5Cdfrac%7B-b%5Cpm%5Csqrt%7B%5CDelta%7D%7D%7B2a%7D%7D%5C%5C%5C%5C%5C%5C%20%5Cmathsf%7Bt%3D%5Cdfrac%7B-1%5Cpm%5Csqrt%7B17%7D%7D%7B2%5Ccdot%202%7D%7D%5C%5C%5C%5C%5C%5C%20%5Cmathsf%7Bt%3D%5Cdfrac%7B-1%5Cpm%5Csqrt%7B17%7D%7D%7B4%7D%7D%5C%5C%5C%5C%5C%5C%20%5Cbegin%7Barray%7D%7Brcl%7D%20%5Cmathsf%7Bt%3D%5Cdfrac%7B-1%2B%5Csqrt%7B17%7D%7D%7B4%7D%7D%26%5Ctextsf%7B%20or%20%7D%26%5Cmathsf%7Bt%3D%5Cdfrac%7B-1-%5Csqrt%7B17%7D%7D%7B4%7D%7D%20%5Cend%7Barray%7D)
You can discard the negative value for
t. So the solution for
(ii) is
![\begin{array}{rcl} \mathsf{t=0}&\textsf{ or }&\mathsf{t=\dfrac{\sqrt{17}-1}{4}} \end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Brcl%7D%20%5Cmathsf%7Bt%3D0%7D%26%5Ctextsf%7B%20or%20%7D%26%5Cmathsf%7Bt%3D%5Cdfrac%7B%5Csqrt%7B17%7D-1%7D%7B4%7D%7D%20%5Cend%7Barray%7D)
Substitute back for
t = sin x. Remember the restriction for
x:
![\begin{array}{rcl} \mathsf{sin\,x=0}&\textsf{ or }&\mathsf{sin\,x=\dfrac{\sqrt{17}-1}{4}}\\\\ \mathsf{x=0+k\cdot 180^\circ}&\textsf{ or }&\mathsf{x=arcsin\bigg(\dfrac{\sqrt{17}-1}{4}\bigg)+k\cdot 360^\circ}\\\\\\ \mathsf{x=k\cdot 180^\circ}&\textsf{ or }&\mathsf{x=51.33^\circ +k\cdot 360^\circ}\quad\longleftarrow\quad\textsf{solution.} \end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Brcl%7D%20%5Cmathsf%7Bsin%5C%2Cx%3D0%7D%26%5Ctextsf%7B%20or%20%7D%26%5Cmathsf%7Bsin%5C%2Cx%3D%5Cdfrac%7B%5Csqrt%7B17%7D-1%7D%7B4%7D%7D%5C%5C%5C%5C%20%5Cmathsf%7Bx%3D0%2Bk%5Ccdot%20180%5E%5Ccirc%7D%26%5Ctextsf%7B%20or%20%7D%26%5Cmathsf%7Bx%3Darcsin%5Cbigg%28%5Cdfrac%7B%5Csqrt%7B17%7D-1%7D%7B4%7D%5Cbigg%29%2Bk%5Ccdot%20360%5E%5Ccirc%7D%5C%5C%5C%5C%5C%5C%20%5Cmathsf%7Bx%3Dk%5Ccdot%20180%5E%5Ccirc%7D%26%5Ctextsf%7B%20or%20%7D%26%5Cmathsf%7Bx%3D51.33%5E%5Ccirc%20%2Bk%5Ccdot%20360%5E%5Ccirc%7D%5Cquad%5Clongleftarrow%5Cquad%5Ctextsf%7Bsolution.%7D%20%5Cend%7Barray%7D)
where
k is an integer.
I hope this helps. =)